Деякі аспекти оцінки стану працевлаштування населення в Україні - Манойленко, Олександр Володимирович; Мох, Мoхамад Аль Джавад (My University, 2018)
В статті розглянуто особливості працевлаштування населення в контексті рівня освіти пошукачів роботи. Визначено вплив рівня освіти на здатність до працевлаштування. Проаналізовано кількість безробітного населення за рівнем освіти. Встановлено, що на ринку праці існують диспропорції у попиті та пропозиції в працевлаштуванні через невідповідність кваліфікаційним вимогам серед пошукачів роботи та вимогами роботодавців. Визначено, що більшість населення в Україні мають вищу освіту, проте вона не відповідає сучасним вимогам, що спричиняє низьку спроможність працевлаштування населення. Визначено пріоритетні групи одержувачів профорієнтаційних послуг згідно з планами заходів з реалізації Концепції державної системи професійної орієнтації населення. Встановлено, що державне регулювання повинно сприяти реалізації заходів, спрямованих на запобігання масовому вивільненню працівників, сприяння мобільності робочої сили та працевлаштуванню населення в регіонах з найвищими показниками безробіття.

The article deals with the features of employment of the population in the context of the level of education of job seekers. The influence of the educational level on the ability to work is determined. The number of unemployed people by the level of education has been analyzed. It has been established that there are disproportions in demand and supply in the labor market due to non-compliance with qualification requirements among job seekers and employers' requirements. It has been determined that the majority of the population in Ukraine has a higher education, but it does not meet modern requirements, which results in poor employment of the population. Priority groups of recipients of vocational guidance services have been identified in accordance with the plans for implementation of the Concept of the state system of professional orientation of the population. It was established that one of the priority areas of employment is the provision of highquality social services to individuals who are not in a position to compete on the labor market on an equal footing and who need social protection. A list of specialties was determined according to the level of demand for specialists. It is proved that in today's conditions there is a reduction of the needs of employers in workers of all professional groups, the growth of employment of the workers of the simplest professions, the sphere of service and trade, reduction of employment of legislators, managers, managers. It is proved that the growth of youth unemployment due to the share of people with both higher and vocational education, the lack of a state strategy for youth employment. It has been determined that the establishment of minimum wages by law, and not through social dialogue, as in most EU countries, increases the scale of the transfer of employees to informal employment or mass layoffs. It was found that one of the factors of low employment of the population is the inconsistency of wages and qualification requirements and competencies of searchers. It has been established that state regulation should facilitate measures aimed at preventing the massive release of workers, promoting labor mobility and job placement in regions with the highest unemployment rates.
Some aspects of evaluation of the state of employment in Ukraine
Keywords: працевлаштування; державне регулювання; рівень освіти; компетентності; ринок праці; кваліфікація; employment; state regulation; level of education; competence; labor market; qualification